Measuring the Success of Village Information Systems using the DeLone and McLean Model - Katili, Muhammad Rifai; Tuloli, Mohamad Syafri; Bau, Rahmat Taufik R.L; Utina, Iin (Jambura Journal of Informatics, 2024)
This study aims to measure the successful implementation of the Village Information System (SID) in Tabongo Village, Gorontalo Regency, using the DeLone and McLean model. This model measures the success of information systems based on six dimensions: system quality, information quality, service quality, usage, user satisfaction, and net benefits. Data were collected through a survey of 267 people (users) of SID in Tabongo Village. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the relationship between the DeLone and McLean model variables. The results showed that system quality, information quality, and user satisfaction positively influence net benefits. Meanwhile, service quality and usage do not significantly affect net benefits. These findings suggest that efforts must be made to improve the quality of services and the use of SID to maximize the community's benefits. Socialization and training for SID users also need to be carried out to improve understanding and skills in using SID.